Antecedents Of Consumer Loyalty In PT. Rentokil Initial Medan Indonesia - Esther Praja Anggriany Panggabean; Winda Sri Astuti Doloksaribu; Maisara Batubara (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
The purpose of this study was to determine and analyze the effect of product quality and service quality on consumer loyalty at PT. Rentokil Initial Indonesia Medan. The method used in this research is a survey approach, this type of research is quantitative descriptive and the nature of this research is explanatory descriptive, data collection is done by questionnaire and documentation study, and data is analyzed using multiple linear regression. The results show that product quality and service quality simultaneously have a positive and significant effect on consumer loyalty, good product quality and service quality will be able to have a real impact on increasing consumer loyalty, and partially each product quality and service quality have a positive and significant effect. to consumer loyalty. The dominant product quality has an effect on consumer loyalty at PT. Rentokil Initial. Keywords: Product Quality, Service Quality, Consumer Loyalty